Lumbar glands in the frog genera Pleurodema and Somuncuria (Anura: Leiuperidae): Histological and histochemical perspectives - Ferraro, Daiana Paola (2013)
The skin in the lumbar region of nine species of Pleurodema and in the monotypic genus Somuncuria (Anura: Leiuperidae) bears macroglands [lumbar gland (LG)]. Lumbar glands of Pleurodema bibroni, P. borellii, P. brachyops, P. bufoninum, P. cinereum, P. cordobae, P. kriegi, and P. thaul, as well as Somuncuria somuncurensis, were examined using histological and histochemical methods. The epidermis and the dermis of LGs are described. Also, skin of LGs presents characteristic features as the interruption of the Eberth-Katschenko layer and the presence of a differentiated type of gland only observed in macrogland and not previously described for Pleurodema or Somuncuria; this is termed lumbar serous gland. These glands are filled with a granular product, which occasionally is immersed in a matrix. Differences in the secretory products of mucous and serous glands are described, as well as inter- and intraspecific variability of gland structure. The mode of toxin expulsion from macroglands and the homology between lumbar and inguinal glands among anuran families are discussed. © 2011 The Authors. Acta Zoologica © 2011 The Royal Swedish Academy of Sciences.